An introduction to International Traditional Medicine Clinical Trial Registry (ITMCTR): A cross-regional registry focusing on theme of traditional medicine - Xuefei Zhang; Ning Liang; Yujing Zhang; Chen Zhao; Lijiao Yan; Ziteng Hu; Sihong Yang; Zehui Ye; Nannan Shi; Yanping Wang; Luqi Huang (Science of Traditional Chinese Medicine)
Abstract. Clinical trials play a crucial role in advancing the field of human health care. The registration of clinical trials can effectively identify potential publication bias and prevent unnecessary duplication of research efforts, serving as a source of transparent data for health care professionals and researchers, enhancing the quality of clinical research, and presenting more transparent, standardized, authentic, and useful clinical trials. To enhance the capacity for evidence production in traditional medicine from the source, the International Traditional Medicine Clinical Trial Registry (ITMCTR), a cross-regional registry focusing on the theme of traditional medicine, was established. Under the current registration background, this study aims to introduce the problems and current status related to clinical trial registration, as well as the features and functions of the ITMCTR. The results of this study illustrate the necessity of establishing a specialized registration platform for traditional medicine to assist researchers in understanding the basic background of registration and relevant information regarding registration platforms, regardless of whether their research is related to traditional medicine or not. Ultimately, the results of this work will help researchers choose the appropriate platform for more efficient and transparent registration.